THE MEANING OF LANGUAGE IN LITERATURE WORKS AS A CULTURE AND EDUCATION TOOL - Faradela Tasya Amalia; Juanda Juanda (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
This study aims to discuss the relation between language and culture and an overview of language realization in literary works as a manifestation of cultural preservation. The research method used to discuss this topic is descriptive method, which provides an overview of the forms of expression in literary works in the form of traditional ceremonies, pupujian, and pupuh. The results of this study indicate that in the traditional open door ceremony which contains teachings and culture that a husband will always try to sacrifice his body and soul for his beloved wife. Pupujian teaches a person for religious education, prayer, warning, and the history of the prophet. Pupuh teaches character education that humans do not indulge in lust, advice to work hard, education to invite children to be devoted to their parents. The impact of the results of this study is that language can be used as a tool in character education for students or the general public. Therefore, character education can be taught implicitly through works produced by writers.